Nutritional requirements for the mycelial biomass and exopolymer production by Hericium erinaceus CZ-2 - Huang, Daming (Array, 2007)
In this work, the effects of medium composition and fermentation parameters on the simultaneous production of mycelial biomass and exopolymer by medicinal mushroom Hericium erinaceus CZ-2 were investigated in shake flask cultures using one-factor-at-a-time method and orthogonal array design. Results showed that the most suitable carbon, nitrogen, mineral sources, and cofactors for the mycelial biomass and exopolymer production were: corn flour combined with 1 % glucose, yeast extract, KH2PO4 and corn steep liquor. The intuitive analysis of orthogonal array design results indicated that the effects of nutritional requirement on the mycelial growth of Hericium erinaceus CZ-2 were in regular sequence of corn flour combined with 1 % glucose > yeast extract > corn steep liquor > KH2PO4, and those on exopolymer production were in the order of corn flour combined with glucose > KH2PO4 > yeast extract > corn steep liquor. The maximal yield of mycelial biomass (16.07 g/L) was obtained when the composition of the culture medium was (in g/L): corn flour 30, glucose 10, yeast extract 3, KH2PO4 1, CaCO3 0.5, and 15 mL/L of corn steep liquor; while the maximal exopolymer yield (1.314 g/L) was achieved when the composition of medium was (in g/L): corn flour 30, glucose 10, yeast extract 5, KH2PO4 3, CaCO3 0.5, and 15 mL/L of corn steep liquor. In the 15-litre scale-up fermentation, the maximum mycelial biomass yield of 20.50 g/L was achieved using the optimized medium